Increasing the Capacity of BUMDes Rekso Wijoyo Tambong Village through Training in Preparing and Organizing Thematic Tourism Packages for Agrotourism, Geotourism and Historical Tourism - Muhamad Ari Perdana; Ayu Wanda Febrian; Adetiya Prananda Putra; Nanda Dwi Saputra (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service investigates the designation of Tambong Village as a Tourist Village by the Banyuwangi Regency Government, focusing on the development of agriculture-based tourism (agrotourism) under the initiative "Ider Galengan Tourism." This program combines educational activities in rice fields with recreational tubing. To enhance the capabilities of BUMDes Rekso Wijoyo in tourism management, a Development Program will be implemented through a Regional Partnership Based Service scheme. This initiative aims to address challenges in creating and marketing thematic tour packages, providing training and resources for effective package preparation, proposal development, and marketing partnerships. The expected outcomes include a comprehensive guidebook and product catalog to support the management and promotion of Tambong Village's tourism offerings.